Detection and kinetics of persistent neutralizing anti-interferon-beta antibodies in patients with multiple sclerosis. Results from the ABIRISK prospective cohort study - Jensen, Poul Erik H; Warnke, Clemens; Ingenhoven, Kathleen; Piccoli, Luca; Gasis, Marcia; Hermanrud, Christina; Fernandez-Rodriguez, Blanca M; Ryner, Malin; Kramer, Daniel; Link, Jenny; Ramanujam, Ryan; Auer, Michael; et al. (Journal of neuroimmunology, 2019)
Two validated assays, a bridging ELISA and a luciferase-based bioassay, were compared for detection of anti-drug antibodies (ADA) against interferon-beta (IFN-β) in patients with multiple sclerosis. Serum samples were tested from patients enrolled in a prospective study of 18 months. In contrast to the ELISA, when IFN-β-specific rabbit polyclonal and human monoclonal antibodies were tested, the bioassay was the more sensitive to detect IFN-β ADA in patients' sera. For clinical samples, selection of method of ELISA should be evaluated prior to the use of a multi-tiered approach. A titer threshold value is reported that may be used as a predictor for persistently positive neutralizing ADA.
Keywords: Immunologic Factors; neutralizující protilátky; Male; Multiple Sclerosis; Interferon-beta; Biological Assay; mužské pohlaví; Neutralization Tests; biotest; ELISA; Enzyme-Linked Immunosorbent Assay; lidé; interferon beta; ženské pohlaví; neutralizační testy; Humans; Antibodies, Neutralizing; imunologické faktory; Female; roztroušená skleróza